2013
DOI: 10.1097/nna.0b013e31828958cd
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Culture of Safety in the Emergency Department

Abstract: Training on teamwork skills can lead to a positive improvement of staff perception related to a culture of safety among emergency department staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 2 publications
8
54
1
1
Order By: Relevance
“…Two individuals indicated that they would be attending the 2015 TeamSTEPPS National Conference to gain a greater understanding of ways to implement the training. Jones et al found that training related to teamwork skills can result in an improvement in staff perceptions of patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Two individuals indicated that they would be attending the 2015 TeamSTEPPS National Conference to gain a greater understanding of ways to implement the training. Jones et al found that training related to teamwork skills can result in an improvement in staff perceptions of patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, TeamSTEPPS has been implemented in many U.S. hospitals. These training programs have been linked to enhanced staff knowledge, skill, and attitudes (Jones, Podila, & Powers, 2013;Sawyer, Laubach, Hudak, Yamamura, & Pocrnich, 2013) as well as improved clinical outcomes (Capella et al, 2010;Spiva et al, 2014). Yet, evidence suggests that TeamSTEPPS interventions are not universally effective (Armour Forse, Bramble, & McQuillan, 2011;Coburn & Gage-Croll, 2014;Sheppard, Williams, & Klein, 2013).…”
Section: Conceptual Frameworkmentioning
confidence: 98%
“…Studies reporting the use of interprofessional practice interventions tended to employ team checklists [28][29], team briefings [30,31] or patient safety rounds [32,33]. Those studies that employed multiple intervention methods blended, for example, team-based training with practice-based activities such as the use of a team briefing [34][35]. The duration of these interventions ranged widely from a few hours of participation in a team training workshop [24] to practice-based interventions which lasted over a number of months [36].…”
Section: Insert Table 2 About Herementioning
confidence: 99%